The Contribution of Population Health and Demographic Change to Economic Growth in China and India - Bloom, David E. (2010)
We find that a cross-country model of economic growth successfully tracks the growth takeoffs in China and India. The major drivers of the predicted takeoffs are improved health, increased openness to trade, and a rising labor force-to-population ratio due to fertility decline. We also explore the effect of the reallocation of labor from low-productivity agriculture to the higher-productivity industry and service sectors. Including the money value of longevity improvements in a measure of full income reduces the gap between the magnitude of China's takeoff relative to India's due to the relative stagnation in life expectancy in China since 1980.